THE ISSUE OF SENATORIAL INSPECTIONS IN THE RUSSIAN EMPIRE AND F. GIRS' REVIEW IN TURKESTAN - Rasulov B.G (Scholar Express Journal, 2025)
This article provides information on the initiation, goals, and objectives of senatorial investigations conducted throughout the governorates of the Russian Empire, the guidelines developed for these investigations, the Russian emperors' attitudes towards investigative work, the commencement of F. Girs' revision in Turkestan, its intended purpose, and its results.
Keywords: Russian Empire; Turkestan Governor-Generalship; Peter I; Senatorial Investigation